Five new species of Chelifera Macquart from China (Diptera: Empididae) - Wang, Jiaojie; Lin, Chen; Yang, Ding (Zootaxa, 2021)
Previously nine species of the genus Chelifera were known to occur in China. Here the following five new species of Chelifera are described from Sichuan; C. acutata sp. nov., C. brevis sp. nov., C. obtusa sp. nov., C. sichuanensis sp. nov., and C. wangi sp. nov. A key to the species of Chelifera from China is provided, and male terminalia and habitus images are included for each new species.